HOW LEARNING FOREIGN LANGUAGES HELPS STUDENTS (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: Learning foreign languages significantly benefits students by fostering cultural awareness, enhancing cognitive and academic performance, and expanding career opportunities. It cultivates global citizenship, improves memory and problem-solving skills, and builds resilience and social connections. In an increasingly interconnected world, foreign language education equips students with essential skills for personal growth and professional success, making it a vital component of modern education.